Hold me, thrill me, kiss me, kill me: the ambivalent queer of post-network television. Issue 2 (3rd April 2019) - Owens, Andrew J.
ABSTRACT: This essay reassesses the deregulation of the American television industry and the rise of identitarian premium cable channels in the context of a new screen presence that has, since the early-2000s, advanced more provocative representations of sexual non-normativity than those found on network programming. This figure, the ambivalent queer of post-network TV, is a libidinous and morally suspect individual often found on premium GLBTQ cable outlets like Here! and on its series such as Dante's Cove (2005–2007). Such channels target niche audiences interested in 'quality' programming and, as a result, are able to offer showrunners and writers a comparatively broad range of creative control, leading to series that break social, cultural, and televisual taboos. And nowhere has this boundary-breaking potential of the ambivalent cable queer been more industrially conspicuous than in television horror.